1998
DOI: 10.1038/sj.onc.1201736
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and immunological analysis of genetic prostate specific antigen (PSA) vaccine

Abstract: Nucleic acid immunization has been investigated as immunotherapy for infectious diseases as well as for treating speci®c types of cancers. In this approach, nucleic acid expression cassettes are directly inoculated into the host, whose transfected cells become the production source of novel and possibly immunologically foreign protein. We have developed a DNA vaccine construct which encodes for PSA by cloning a cDNA for PSA into a mammalian expression vector under control of a CMV promoter. We investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 27 publications
0
30
0
2
Order By: Relevance
“…PSA-DNA vaccination leads to the generation of T-cell responses to PSA in BALB/c mice, 8 and BALB/c mice vaccinated with PSA-expressing P815 tumor cells were protected against a subsequent challenge with a histocompatible PSA-expressing lung carcinoma, and vice versa. 9 When rhesus monkeys were immunized with a recombinant vaccinia vector expressing PSA, a brief IgM response to PSA as well as specific T-cell proliferation was detected.…”
mentioning
confidence: 99%
“…PSA-DNA vaccination leads to the generation of T-cell responses to PSA in BALB/c mice, 8 and BALB/c mice vaccinated with PSA-expressing P815 tumor cells were protected against a subsequent challenge with a histocompatible PSA-expressing lung carcinoma, and vice versa. 9 When rhesus monkeys were immunized with a recombinant vaccinia vector expressing PSA, a brief IgM response to PSA as well as specific T-cell proliferation was detected.…”
mentioning
confidence: 99%
“…16 It has been shown that human cytotoxic T lymphocytes (CTLs) respond to peptides derived from PSA 17 and that intramuscular immunization of mice with plasmid DNA encoding PSA also leads to potent CTL responses to specific tumor cells. 18 Furthermore, a preponderance of antibody responses were found to be directed to PSA antigens when general mRNA from a prostate tumor line was used to transfect autologous DCs. 19 In sum, these studies indicate that PSA is a valid antigen for potential prostate cancer immunotherapy strategies.…”
mentioning
confidence: 99%
“…Although the efficacy of PSAspecific peptides pulsed onto DC to induce CTL has not been reported to date, a conceptually superior approach would entail the targeting of multiple class I and class II epitopes present on the PSA molecule, which are thought to further stabilize or maintain effective T cell responses in vivo (7,8).…”
mentioning
confidence: 99%